2021
DOI: 10.3998/tia.17063888.0039.308
|View full text |Cite
|
Sign up to set email alerts
|

What Happens When You Close the Door on Remote Proctoring? Moving Toward Authentic Assessments with a People-Centered Approach

Abstract: The COVID-19 pandemic made traditionally proctored in-person exams impossible. This article provides a summary of the arguments against institutional adoption of remote proctoring services with a focus on equity, an account of the decision to avoid remote proctoring on the University of Michigan-Dearborn campus, and conclusions and suggestions for other teaching and learning professionals who would like to take a similar approach. Remote proctoring services require access to technology that not all students ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 10 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…These overly positive indicators explain that most students would like to repeat remote assessment, despite the fact that the remote proctoring method initially generated enormous mistrust among students, as Silverman et al [54] have shown in their study. Once the initial uncertainty is overcome, the digital environment is reliable and safe for the student.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These overly positive indicators explain that most students would like to repeat remote assessment, despite the fact that the remote proctoring method initially generated enormous mistrust among students, as Silverman et al [54] have shown in their study. Once the initial uncertainty is overcome, the digital environment is reliable and safe for the student.…”
Section: Discussionmentioning
confidence: 86%
“…The remote proctoring system has generated great controversy since its use has been extended in the university sector during the COVID-19 pandemic. For example, Silverman et al [54] show in their study a summary of the arguments against institutional adoption of remote proctoring services with a focus on equity, an account of the decision to avoid remote proctoring on the University of Michigan. This software, once installed, activates the student's webcam and executes certain prior steps: a short recording of the user, a picture of the student and his ID, and a recording of the student's environment [53].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the initiatives from the universities or the government that normalize the recording of students in the development of evaluations and the monitoring of their computers, facts that may lead to ethical problems and possible conflicts with the European standards of the General Data Protection Regulation (GDPR), as can be seen in previous studies [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126]; the distributors of these e-proctoring systems have already proposed guidelines in this regard that allow them to comply with said regulations [127], and the responsibility would fall on the universities to provide their approval of these guidelines or indicate if they see other more fitting ones.…”
Section: Discussionmentioning
confidence: 99%
“…At an institutional level, rather than investing in simple yet costly solutions to address cheating, universities might finance centers for teaching and learning, led by pedagogical experts. At the University of Michigan-Dearborn, for example, after making a collective decision not to use online remote proctoring, the administration invested instead in instructional designers to aid faculty in the creation of authentic, or "people-centered," assessments for their remote classes (Silverman et al, 2021). Though faculty are highly valued subject-area specialists, by and large, most receive little to no training around assessment and instruction (Blouin & Moss, 2015).…”
Section: Final Thoughts and Steps Forwardmentioning
confidence: 99%